Engireering A complier / by Keith D. Cooper and Linda Torczon - Cooper, Keith D; Torczon, Linda (Cambridage : Elsesvier, 2023)
Engineering a Compiler, Third Edition covers the latest developments in compiler technology, with new chapters focusing on semantic elaboration (the problems that arise in generating code from the ad-hoc syntax-directed translation schemes in a generated parser), on runtime support for naming and addressability, and on code shape for expressions, assignments and control-structures. Leading educators and researchers, Keith Cooper and Linda Torczon, have revised this popular text with a fresh approach to learning important techniques for constructing a modern compiler, combining basic principles with pragmatic insights from their own experience building state-of-the-art compilers.
Incudes biography and index
Keywords: Scanners; Synteax- Driven translation; Code shape